2005
DOI: 10.1029/2004gb002422
|View full text |Cite
|
Sign up to set email alerts
|

Transport of organic carbon from the California coast to the slope region: A study of Δ14C and δ13C signatures of organic compound classes

Abstract: [1] Surface sediments along a transect from an abyssal site in the northeastern Pacific (Station M, 34°50 0 N, 123°00 0 W) to a small mountainous river on the California coast (Santa Clara River) were studied to investigate the sources and cycling of organic matter on the continental margin. Sediment samples were separated into organic compound fractions (extractable lipids, amino acids (THAA), carbohydrates (TCHO), and the acid-insoluble fraction), and their carbon isotope ratios were measured. The D 14 C val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…The persistence of noncontemporary radiocarbon compositions of fl uvial dissolved and particulate organic carbon phases, certain lipid fractions, and shallow sedimentary OC in an array of margin systems imply that some fossil material is able to evade complete remineralization (Goñi et al, 2005;Hwang et al, 2005;Komada et al, 2004Komada et al, , 2005Bauer, 2001a, 2001b;Yunker et al, 2005). While bacterial assimilation of petrogenic carbon has been demonstrated (Petsch et al, 2001, a signifi cant portion might be effi ciently recycled through the modern environment and undergo reburial in shelf sediments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The persistence of noncontemporary radiocarbon compositions of fl uvial dissolved and particulate organic carbon phases, certain lipid fractions, and shallow sedimentary OC in an array of margin systems imply that some fossil material is able to evade complete remineralization (Goñi et al, 2005;Hwang et al, 2005;Komada et al, 2004Komada et al, , 2005Bauer, 2001a, 2001b;Yunker et al, 2005). While bacterial assimilation of petrogenic carbon has been demonstrated (Petsch et al, 2001, a signifi cant portion might be effi ciently recycled through the modern environment and undergo reburial in shelf sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies, primarily based on carbon isotopic measurements of total organic carbon (TOC) and its component compound classes, have suggested that petrogenic material (Δ 14 C = -1000‰) weathered from uplifted shales might contribute a signifi cant portion of the recalcitrant organic matter delivered to the oceans (Blair et al, 2003(Blair et al, , 2004Dickens et al, 2004;Goñi et al, 2005;Hwang et al, 2005;Komada et al, 2004Komada et al, , 2005. The persistence of noncontemporary radiocarbon compositions of fl uvial dissolved and particulate organic carbon phases, certain lipid fractions, and shallow sedimentary OC in an array of margin systems imply that some fossil material is able to evade complete remineralization (Goñi et al, 2005;Hwang et al, 2005;Komada et al, 2004Komada et al, , 2005Bauer, 2001a, 2001b;Yunker et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It also represents the largest reservoir of organic matter on Earth at 15 x 1021 g ) (see Figure 4.1 in Chapter 4 of this thesis), from which perhaps 1014 g may be released each year ) through a combination of physical erosion and selective oxidation (Petsch et al, 2000(Petsch et al, , 2001a. Indeed, the persistence of non-contemporary radiocarbon ages in fluvial DOC, POC, bulk lipid fractions, and shallow sedimentary OC in an array of margin systems imply that some fossil material is able to evade further remineralization in these settings (Raymond and Bauer, 2001a,b;Komada et al, 2004Komada et al, , 2005Hwang et al, 2005;Yunker et al, in press). …”
Section: Introductionmentioning
confidence: 99%
“…Recent, primarily 14 C-based studies have also suggested that petrogenic OC (also known as fossil OC or kerogen) weathered from organic-rich sedimentary rocks (shales) might comprise a significant portion of the organic matter currently buried in certain shelf sediments Dickens et al, 2004;Komada et al, 2004Komada et al, , 2005Hwang et al, 2005). This material is radiocarbon 'dead' (A' 4 C = -1000 %o), presumably largely refractory, and likely associated with clay-sized minerals, having experienced late diagenetic and catagenetic modification in the lithosphere for > 106 years.…”
Section: Introductionmentioning
confidence: 99%
“…For the majority of surface sediments examined in this study, the ∆ , 1993;Wang et al, 1996;Hwang et al, 2005;Komada et al, 2005). Salt marsh sediments from WF are, however, more enriched (+44‰, Figure 4.2c), likely due to incorporation of recently synthesized vascular plant biomass from the roots of the marsh grass Spartina 87 pre-aged soil material and bitumen or kerogen in MS and BS sediments Drenzek et al, 2005) and from relict organic carbon from the Antarctic continent in the case of RS sediments .…”
Section: General Trends In Surface Sedimentsmentioning
confidence: 99%